AN MS EXCEL TOOL FOR WASTEWATER TREATMENT MODELING IN UNDERGRADUATE EDUCATION: ACTIVATED SLUDGE MODEL NO. 1 - Manav-Demir, Neslihan; Demir, Selami (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
In this study, an MS Excel Visual Basic for Applications (VBA) program was implemented for dynamic modeling of carbon oxidation and nitrification-denitrification processes in wastewater treatment plants. Activated Sludge Model No. 1 (ASM1) was used for this purpose. A user interface was also prepared with features in MS Excel sheet. The program is intended to help teaching the students the fundamentals of unit processes that take place in biological nitrogen removal systems. A settling model was also incorporated into the model assuming a ten layer secondary settling tank. Takacs' double exponential model was employed to estimate solids settling velocities in each layer. The MS Excel tool allows the user to define the system configuration, the flowrates, the influent wastewater characterization as well as stoichiometric and lcinetic coefficients in ASM1. Besides, wastewater temperature, settler's design, maximum simulation time, reporting frequency, and step size in the solution are designated as user inputs. Component concentrations in each reactor as well as in effluent are calculated by the tool. An AO process configuration was defined and simulated using the new tool both using complete-mix and plug-flow regimes. The new tool successfully proves itself an excellent tool for undergraduate education in environmental engineering.
Keywords: Activated Sludge Model No. 1; Takacs model; Biological nitrogen removal; MS Excel; Engineering education; VERIFICATION; PARAMETERS; Environmental Sciences & Ecology